Outpatient Registration Staff Performance Assessment Model Using Ongoing Professional Practice Evaluation Method - Budi, Savitri Citra; Yuni Suryaningsih; Caecilia Kayla Selomitha Sigit; Elisa Wahyuningsih; Hasna' Shofiyyah; Iffah Khoirul Janah; Nadia Dwi Cahyati; Annisa Maulida Ningtyas (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2024)
Ensuring patient safety and improving hospital quality begins with the patient admission process. Patient misidentification can significantly contribute to patient safety incidents; therefore, monitoring the performance of patient admission staff is crucial in preventing adverse events. Staff performance assessment includes evaluation of attitude, professional development, and service performance. This study aims to develop a performance assessment model based on the Ongoing Professional Practice Evaluation (OPPE) method. This study utilized a qualitative approach with an exploratory design. Data were collected through observations, interviews, document reviews, and surveys. Four staff members from outpatient admissions participated in the study. The study outlined assessment components consisting of attitude (7 aspects), professional development (3 aspects), and service performance (23 aspects). Self-assessment results showed all staff demonstrated competence in attitude and service delivery, while a minority lacked competence in professional development. The outpatient admission staff performance assessment model, based on the Ongoing Professional Practice Evaluation (OPPE) method, integrates three aspects (attitude, professional development, and service performance) and can be effectively implemented in hospitals to evaluate and monitor service quality.